2018
DOI: 10.1108/ara-01-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the development of accounting practices in Jordan: an institutional perspective

Abstract: Purpose Based on the institutional theory, the purpose of this paper is to examine institutional factors that affect the development of accounting practices in Jordan. Design/methodology/approach The current study surveys the perceptions of 306 participants and 20 interviewees. Findings First, the early formation of accounting practices in Jordan has been affected by the legacy of Ottoman Empire’s and the British Colony’s accounting systems. Second, the results indicate that government of Jordan (regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
(56 reference statements)
1
30
0
1
Order By: Relevance
“…Those nations are deemed to be responding to coercive pressures stemming from the regulatory requirements of major international agencies, such as the World Bank and International Monetary Fund (IMF). Similar results were found by Tahat, Omran, and AbuGhazaleh (2018) in the case of Jordan, where pressures exerted by these international donors were identified has a significant coercive pressure. Normative and mimetic pressures exerted by Big 4 accounting firms and the UAE's trading partners were identified (Irvine, 2008).…”
Section: They Focused On Institutional Pressures That Explained the Dsupporting
confidence: 82%
See 1 more Smart Citation
“…Those nations are deemed to be responding to coercive pressures stemming from the regulatory requirements of major international agencies, such as the World Bank and International Monetary Fund (IMF). Similar results were found by Tahat, Omran, and AbuGhazaleh (2018) in the case of Jordan, where pressures exerted by these international donors were identified has a significant coercive pressure. Normative and mimetic pressures exerted by Big 4 accounting firms and the UAE's trading partners were identified (Irvine, 2008).…”
Section: They Focused On Institutional Pressures That Explained the Dsupporting
confidence: 82%
“…As Mir and Rahaman (2005) argue, a highly problematic aspect of the adoption of IFRS centres on the process of implementation. In emerging and developing economies, the educational processes during implementation of IFRS is very significant in embedding new practices because those countries generally have a lower-skilled cohort of accounting professionals (Albu et al, 2013;Albu et al, 2014;Nurunnabi, 2015;Tahat, Omran, & AbuGhazaleh, 2018). Additionally, if undemocratic decision processes exclude interested parties and a coordinated structure is absent (Mir & Rahaman, 2005), this can result in corruption, weak enforcement mechanisms, and low levels of compliance with IFRS (Nurunnabi, 2015).…”
Section: Limitations Of Existing Literature On Ifrs Adoption and Implmentioning
confidence: 99%
“…Jordan is a developing but politically stable Arab nation with an open market economy and strong socio-economic ties with other countries. Over the last two decades, the government has embarked on different financial market reforms to improve Jordan's reputation as an open economy (Tahat et al, 2018) and ensure economic stability. Of all the Middle Eastern countries, Jordan is considered the most competitive and liberal, due to its adoption of more liberal policies to improve the national economy.…”
Section: Ifrs Implementation In Jordanmentioning
confidence: 99%
“…Therefore, the borrowing economy is subject to contractual agreement from these International financial reporting standards nongovernmental lending/donating organizations that are seeking to bring about change through foreign aid (Hassan et al, 2014). Consequently, countries requiring foreign aid to develop infrastructure normally have little choice but to adopt IFRS, as it is often a condition of funding (Mir and Rahaman, 2005;Tahat et al, 2018). Encouraging the adoption of IAS is evidence of how international lenders, through their lending activities, are influencing accounting practices globally (Mir and Rahaman, 2005).…”
Section: Intra-organizational Dynamicsmentioning
confidence: 99%
“…Furthermore, Mir and Rahaman (2005)'s research on Bangladesh found that the pressure exerted by key international donor/lending institutions on the Bangladeshi government was a major factor driving the decision to adopt IAS. Tahat et al (2018) recently showed that pressure from international donors has pushed Jordan to adopt IFRS.…”
Section: Intra-organizational Dynamicsmentioning
confidence: 99%